Can Family Ownership Strengthen the Relationship Between Intellectual Capital and Performance in ASEAN High-Tech Firms? - Bima Cinintya Pratama; Maulida Nurul Innayah (International Journal of Business and Society, 2021)
This study investigates the positive relationship between intellectual capital and firm performance. It examines whether family ownership can strengthen the relationship between intellectual capital and firm performance of firms in high-technology industries in ASEAN. The data was collected from the BvD OSIRIS database and company annual reports from 2008-2014 and conducted on five countries in ASEAN, namely Indonesia, Malaysia, Philippines, Singapore, and Thailand. The final sample used in this study consists of a total of 1,310 observations. This study uses panel data regression model analysis, i.e. fixed effect regression and random effect regression. The results showed that intellectual capital has a positive relationship with financial performance. The result proved the role of intellectual capital in increasing firm finances and its importance as one of the primary resources in competing in the AEC challenges and as the firm's primary driver for the firm's success. It is not found in the relationship between intellectual capital and market performance. In the interaction relationship, the result is contrary to the alignment effect that becomes our previous prediction. The result is consistent with the entrenchment effect and indicates that family ownership can weaken the relationship between intellectual capital and financial performance. There is no evidence about the relationship between the interaction of intellectual capital and family ownership on market performance.